(3JMGhjd Sfi GdehGdjO hTghQgG hCjGegGs - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s
(3ChdgG (B:s
(3Ef YGeI GdeJbOejf ef CUMGH UfGYI GdfLhe cJH cd hGMO efge cJGHkG ai JMGhjd Sfi GdehdhO hTghQgG hCjGegG ; EdG Cf HYVge PcQ TjFkG de jPcQg ZjQg s
(3BNQgG (B:s
(3hef MGd ai faSg , hef ehVYg ef HQLg ef HjhJ GdYdd, hef ehGVY GdfhGXQ Edjg hMGdGJgG , hGddg CYde Je GdcJGH HMeO Gddg s
(3ai JSY ebGdGJ hSJI hJSYjf aUdkGs
(3fSNI YJjbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B148s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B251 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B395 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs